LIVESTOCK INVESTMENT AND ITS IMPACT ON FARM INCOME AMONG MIXED FARMERS IN NAGALAND - SUNGJEMINLA LONGKUMER; B. KILANGLA JAMIR (The Journal of Research ANGRAU, 2025)
The study estimates the pattern of livestock investment and its impact on farm income  among mixed farmers of Nagaland. Additionally, the study also incorporates other livelihood assets  owned by livestock farmers to identify the extent of their influence on farm income. The primary  data pertains to the year 2020-21, collected through a multi-stage sampling technique conducted  in Peren district of Nagaland, known as the “Green District of Nagaland” because of high diversity of flora and fauna offering significant potential abundant grazing areas. Information from 197 mixed farmers were collected to generate and interpret results. On average, farm households invest ¹ 38,293.75 annually in livestock, which constitutes about 27.75 per cent of total agricultural investment, with livestock contributing 40.33 per cent to total farm income. By farm size, the proportion of livestock investment in total farm investment was lower for marginal (29.27 per cent) and small farmers (21.79 per cent) than for medium farmers (33.64 per cent). Consequently, medium farmers earn a more significant proportion of income from livestock (46.03 per cent). Regression analysis results revealed that livestock investment, farm size, level of farmers participation in livestock management, and number of animals have positive impact on farm business income.The study suggests that there is catalyst for appropriate and higher government investment in agriculture and livestock operations by incorporating traditional knowledge and experience with the latest technologies.